1990
DOI: 10.1128/mcb.10.6.3105
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of factors that direct transcription of rat ribosomal DNA.

Abstract: The protein components that direct and activate accurate transcription by rat RNA polymerase I were studied in extracts of Novikoff hepatoma ascites cells. A minimum of at least two components, besides RNA polymerase I, that are necessary for efficient utilization of templates were identified. The first factor, rat SL-1, is required for species-specific recognition of the rat RNA polymerase I promoter and may be sufficient to direct transcription by pure RNA polymerase I. Rat SL-1 directed the transcription of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
122
1

Year Published

1991
1991
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 44 publications
5
122
1
Order By: Relevance
“…That region of the promoter ( 31 to + 6) sufficient for transcription in vitro, and essential for transcription in vivo is referred to as the core promoter element (CPE). However, when 5'-deletion mutant and wild-type promoters compete against one another under conditions where the levels of the transcription factors are limiting, a requirement for distal sequences becomes apparent (5,12). In vivo experiments demonstrate that constructs with only the CPE are essentially inactive (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That region of the promoter ( 31 to + 6) sufficient for transcription in vitro, and essential for transcription in vivo is referred to as the core promoter element (CPE). However, when 5'-deletion mutant and wild-type promoters compete against one another under conditions where the levels of the transcription factors are limiting, a requirement for distal sequences becomes apparent (5,12). In vivo experiments demonstrate that constructs with only the CPE are essentially inactive (7).…”
Section: Introductionmentioning
confidence: 99%
“…Functional analyses of the elements of the promoters of the vertebrate rRNA genes demonstrates that despite significant sequence differences, the promoters appear to consist of at least two or possibly three elements which function homologously (4,5,6). That region of the promoter ( 31 to + 6) sufficient for transcription in vitro, and essential for transcription in vivo is referred to as the core promoter element (CPE).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, however, UBF is not required for SLI to bind the promoter (34,35) but both factors still interact to form a footprint more extensive than either activity alone (13). Furthermore, several studies have revealed that mouse rRNA transcription is greatly *To whom correspondence should be addressed Q--n) 1994 Oxford University Press stimulated by UBF apparently by acting early in the assembly of stable pre-initiation complexes (10,15,18,34). It has been proposed that UBF acts as both an activator, by stabilizing the interaction of the TBP-containing activity and/or RNA polymerase I with the promoter and as an anti-repressor by preventing histone (or other DNA binding factors) mediated repression (35,36).…”
mentioning
confidence: 99%
“…In human extracts the pol I transcription activity named SL1 [Selectivity Factor 1; (26)] contains TBP and at least three TBPAssociated Factors (TAFs) (27). In other species the equivalent activity has been named TFID, Factor D, Rib-I or TIF-1B (15,18,(28)(29)(30)(31)(32). Human SLI requires interaction with UBF to form a promoter complex which can be visualized as a DNase I footprint that is more extensive than the footprint produced by UBF (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation